The Bloodshed in North Halmahera: Roots, Escalation, and Reconciliation - Usman Usman (Journal of Indonesian Social Sciences and Humanities, 2016)
This paper aims to explain the conflict on North Maluku Island or North Halmahera in 1999 to be more specifc. When compared with the conflict in Ambon, the conflict in North Halmahera is much greater in terms of the number of victims and material losses. There are several factors that influenced the conflict such as politics, economics and religion. It seems that politics and religion were the dominant underlying factors of the conflict. At that time, the mass media did not report the conflict e?ectively, so that the resolution of the conflict came too late and the conflict escalated and spread to the entire region of North Maluku. The most fundamental thing causing the conflict was associated with regional growth (pemekaran), namely the emergence of a new sub-district within the existing sub-district of Kao. The new sub-district was created by the Makian, who are migrants from the island of Kie Besi in North Maluku. They pushed the government to establish a new sub-district of Makian Daratan within the sub-district of Kao. The Pagu people, natives to the area, rejected the regional growth. There was a demonstration that ended in a fight between the Pagu and the Makian. Coincidentally, most of the Pagu are Christian and all of the Makian areMuslim. This led to religious issues becoming a factor with certain parties. As a result, this was a horizontal conflict wrapped with religious issues. In terms of methodology, this paper was written using a qualitative approach that produces descriptive data about the conflicts in North Halmahera. The analysis of the field data was undertaken using some theories of conflict. As a conclusion it can be stated that the conflict in North Halmahera is basically a conflict of interest that is wrapped with religious issues.